Are Learning Styles Relevant to Virtual Reality? - Chen, Chwen Jen; Toh, Seong Chong; Wan Mohd, Fauzy Wan (ERIC, 2005)
This study aims to investigate the effects of a virtual reality (VR)-based learning environment on learners with different learning styles. The findings of the aptitude-by-treatment interaction study have shown that learners benefit most from the VR (guided exploration) mode, irrespective of their learning styles. This shows that the VR-based environment offers promise in accommodating individual differences in terms of learning style. In addition, the significant positive effect of the VR (guided exploration) mode--which provides additional navigational aids over the VR (non-guided exploration) mode--which does not provide additional navigational aids--also implies the importance of providing VR-based learning environments with proper instructional design to achieve the desired educational outcomes.